2021
DOI: 10.1111/psyg.12709
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between financial well‐being, life satisfaction, and cognitive function among low‐income community‐dwelling older adults: the moderating role of sex

Abstract: Background Low financial well‐being is a common predicament among older adults living in poverty. The existing literature suggests a correlation between financial well‐being and mental health in old age. Therefore, this study aimed to identify the relationships among financial well‐being, life satisfaction, and cognitive function among low‐income older adults and to examine the moderating effect of sex on these relationships. Methods This study involved 2004 nationally representative community‐dwelling older M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…This study found a positive relationship between life satisfaction and cognitive function, which was consistent with the results of previous studies. A Malaysian cross-sectional study showed that financial satisfaction could increase general life satisfaction and further promote cognitive function among the low-income community-dwelling older adults ( Foong et al, 2021 ). Peitsch et al conducted a prospective cohort study and demonstrated that lower overall life satisfaction was a strong risk factor for developing dementia within the next five years ( Peitsch et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study found a positive relationship between life satisfaction and cognitive function, which was consistent with the results of previous studies. A Malaysian cross-sectional study showed that financial satisfaction could increase general life satisfaction and further promote cognitive function among the low-income community-dwelling older adults ( Foong et al, 2021 ). Peitsch et al conducted a prospective cohort study and demonstrated that lower overall life satisfaction was a strong risk factor for developing dementia within the next five years ( Peitsch et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…One limitation was the use of two spatial cognition tests, one processing speed test, and one WM test. Future research could clarify if other important cognitive function domains (e.g., verbal fluency) [ 7 , 110 ]) would be related to LS with comprehensive multiple-item cognitive tests. Subsequent studies should also include subjective cognitive function measures since they may differ from performance-based ones and function as early warning signs of incident dementia [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aside from that, the poverty status was determined by Malaysia’s poverty line income. Respondents with a household income of less than MYR2,629 were considered living in poverty or in the bottom 40% of Malaysians’ household income, also known as the B40 group [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%